Olfactory System Morphology Suggests Colony Size Drives Trait Evolution in Odorous Ants (Formicidae: Dolichoderinae) - Godfrey, R. Keating; Oberski, Jill T.; Allmark, Taylor; Givens, Caleb; Hernandez-Rivera, Jessica; Gronenberg, Wulfila (Frontiers in Ecology and Evolution, 2021)
In social insects colony fitness is determined in part by individual worker phenotypes. Across ant species, colony size varies greatly and is thought to affect worker trait variation in both proximate and ultimate ways. Little is known about the relationship between colony size and worker trait evolution, but hypotheses addressing the role of social structure in brain evolution suggest workers of small-colony species may have larger brains or larger brain regions necessary for complex behaviors. In previous work on odorous ants (Formicidae: Dolichoderinae) we found no correlation between colony size and these brain properties, but found that relative antennal lobe size scaled negatively with colony size. Therefore, we now test whether sensory systems scale with colony size, with particular attention to olfactory components thought to be involved in nestmate recognition. Across three species of odorous ants, Forelius mccooki, Dorymyrmex insanus, and D. bicolor, which overlap in habitat and foraging ecology but vary in colony size, we compare olfactory sensory structures, comparing those thought to be involved in nestmate recognition. We use the visual system, a sensory modality not as important in social communication in ants, as a control comparison. We find that body size scaling largely explains differences in eye size, antennal length, antennal sensilla density, and total number of olfactory glomeruli across these species. However, sensilla basiconica and olfactory glomeruli in the T6 cluster of the antennal lobe, structures known to be involved in nestmate recognition, do not follow body size scaling observed for other structures. Instead, we find evidence from the closely related Dorymyrmex species that the larger colony species, D. bicolor, invests more in structures implicated in nestmate recognition. To test for functional consequences, we compare nestmate and non-nestmate interactions between these two species and find D. bicolor pairs of either type engage in more interactions than D. insaus pairs. Thus, we do not find evidence supporting a universal pattern of sensory system scaling associated with changes in colony size, but hypothesize that observed differences in the olfactory components in two closely related Dorymyrmex species are evidence of a link between colony size and sensory trait evolution.